2016
DOI: 10.1136/sextrans-2016-052677
|View full text |Cite
|
Sign up to set email alerts
|

Emerging viral STIs among HIV-positive men who have sex with men: the era of hepatitis C virus and human papillomavirus

Abstract: The number of infectious disease outbreaks and the number of unique pathogens responsible have significantly increased since the 1980s. HIV-positive men who have sex with men (MSM) are a vulnerable population with regards to the introduction, spread and clinical consequences of (newly introduced) STIs. After the introduction of combination antiretroviral treatment (cART), the incidence of sexually acquired hepatitis C virus (HCV) infection and human papillomavirus (HPV)-induced anal cancers have significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 61 publications
(87 reference statements)
0
11
1
Order By: Relevance
“…HCV infections are generally uncommon in the Netherlands, with a chronic HCV prevalence of < 0.2% in 2016 [4]. However, an increase in the number of acute HCV infections and reinfections among men who have sex with men (MSM) who are human immunodeficiency virus (HIV)-positive has been reported since early 2000 [5][6][7]. Detection, diagnosis and registration of acute HCV infections are crucial to measure trends in the epidemic and to plan appropriate public health and clinical interventions, such as prevention programmes for those at risk, targeted testing, increasing treatment uptake, and contact tracing to reduce subsequent transmission.…”
Section: Introductionmentioning
confidence: 99%
“…HCV infections are generally uncommon in the Netherlands, with a chronic HCV prevalence of < 0.2% in 2016 [4]. However, an increase in the number of acute HCV infections and reinfections among men who have sex with men (MSM) who are human immunodeficiency virus (HIV)-positive has been reported since early 2000 [5][6][7]. Detection, diagnosis and registration of acute HCV infections are crucial to measure trends in the epidemic and to plan appropriate public health and clinical interventions, such as prevention programmes for those at risk, targeted testing, increasing treatment uptake, and contact tracing to reduce subsequent transmission.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, sexual activities such as anal intercourse were more common among those who were HIV‐infected, while lack of condom use was highly cited by HCV monoinfected and healthy subjects. A study in men who have sex with men showed an increase in HCV cases in HIV + individuals, mainly due to the practice of unprotected anal sex . Some studies have shown that high‐risk populations, such as individuals who have received transfusion and sexually at‐risk individuals, may present falsely reactive results for anti‐HCV detection, which could be the product of cross‐reactivity with other infections, such as HIV or HBV …”
Section: Discussionmentioning
confidence: 99%
“…A study in men who have sex with men showed an increase in HCV cases in HIV + individuals, mainly due to the practice of unprotected anal sex. 29 Some studies have shown that high-risk populations, such as individuals who have received transfusion and sexually at-risk individuals, may present falsely reactive results for anti-HCV detection, which could be the product of cross-reactivity with other infections, such as HIV or HBV. [30][31][32] Anti-HCV testing in DBS and saliva demonstrated specificity above 90% in HCV and HIV monoinfected groups, which is similar to previous studies using DBS in chronic HCV cases 12,[23][24][25]33 and studies using the Salivette device in individuals with chronic hepatitis C and HIV-infected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis C virus (HCV) infections are generally uncommon in the Netherlands, with a chronic HCV prevalence of <0.2% [1]. However, an increase in the number of acute HCV infections and reinfections among men who have sex with men (MSM) who are HIV-positive has been reported since early 2000 [2][3][4]. Detection, diagnosis and registration of acute HCV infections are crucial to measure trends in the epidemic, and plan appropriate public health and clinical interventions, such as prevention programs for those at risk, targeted testing, increasing treatment uptake, and contact tracing to reduce subsequent transmission.…”
Section: Introductionmentioning
confidence: 99%